1989
DOI: 10.1107/s0108768189001138
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer and three-centre bonding in monoprotonated and diprotonated 2,2'-bipyridylium decahydro-closo-decaborate(2–)

Abstract: X-ray difference densities have been measured for the diprotonated form of the title compound at room temperature and for its monoprotonated analogue at 100 K. Atomic charges were determined by Hirshfeld's method of partitioning the difference density in proportion to atomic densities. Roughly 1.6 electrons are transferred to the B~oHl0 unit, and distributed widely over the cluster as a whole. That charge is less than the formal value of 2.0 electrons by an amount which correlates inversely with the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“…Monoprotonated 2,2'-bipyridinium cations have been identified in many earlier crystal structure studies (Khan, Kumar & Tuck, 1984). The present work, as with those of earlier authors, shows that in the crystal lattice, the cation adopts a configuration in which the two N atoms are syn, in contrast to the anti stereochemistry found in the neutral molecule (Merritt & Schroeder, 1956) and in the diprotonated cation (Chantler & Maslen, 1989). The geometry of the monopositive cation is generally close to that of the neutral compound.…”
supporting
confidence: 88%
“…Monoprotonated 2,2'-bipyridinium cations have been identified in many earlier crystal structure studies (Khan, Kumar & Tuck, 1984). The present work, as with those of earlier authors, shows that in the crystal lattice, the cation adopts a configuration in which the two N atoms are syn, in contrast to the anti stereochemistry found in the neutral molecule (Merritt & Schroeder, 1956) and in the diprotonated cation (Chantler & Maslen, 1989). The geometry of the monopositive cation is generally close to that of the neutral compound.…”
supporting
confidence: 88%
“…Die Wasserstoffbru È cken-Bindungen in 3 sind mit Absta È nden von 289 und 266 pm im Vergleich zur Summe der van der Waals-Radien von 318 pm [8] naturgema È û schwa È cher als in den Chloriden. Dies spie- (2) 177,5 (1) (1) 85 (2) 95(4) 98(8) N±H (2) 86 (2) 82 (3) 85 (8) Cl´´´H (1) 239 (2) 226 (3) [I(1)´´´H (2)] 289(8) Cl i´´´H (2) 241 (2) 248 (3) [I(1 a)´´´H (1)] 266 (8) N±P±C (1) 108,02 (6) 106,11 (15) 108,2(8) N±P±C (2) 107,55 (6) (1) 113,2 (11) 113 (2) 102 (8) (6), CCDC-132483 (7), CCDC-132394 (8), CCDC-132431 (9) und CCDC-132432 (10) (1) 163,0(2) P(2)±N (2) 163,0(2) P(1)±C (1) 181,2(3) P(2)±C (7) 179,4(3) P(1)±C (3) 179,0(3) P(2)±C(9) 180,9(3) P(1)±C (5) 178,0(3) P(2)±C(11) 177,7(3) N(1)±H (11) 83 ( …”
unclassified
“…H-N bonds realized between the BH groups of the boron clusters and N-containing cations or molecules. The closest to the present study's detailed discussion of this type of bonds was reported for salts of the closo-decaborate anion with monoprotonated and diprotonated bipyridine [ [32,33], respectively, which were studied by X-ray diffraction; atomic charges were determined by the Hirshfeld's method. The authors reported the difference density maps and discussed the electron distribution of the electron density and the electron transfer between the boron cluster and the cation.…”
Section: Introductionmentioning
confidence: 75%